Patient’s Knowledge of Medications Misadventure Information in Saudi Arabia - Alomi, Yousef Ahmed; Alaskari, Dima Ahmad; Almelf, Malak Mohammad; Badawi, Dima Ali; Alshihri, Abdullah Mohammad (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the Patient’s Knowledge of Medications Misadventure Information in Saudi Arabia. Methods: It is a 4-months cross-sectional survey of patient and Drug-related problem information in Saudi Arabia. The survey consisted of two-part, demographic data and second part forty-nine questions divided into four domains. It included domain 1: necessary information about patient medication, domain 2: patient information about the drug-related problem, domain 3: patient information about drug-related cost and domain 4: patient perception of medications. Midline Plus health information and DailyMed elements information from National Institute of Health United State of America used. The 5-point Likert response scale system was used. The survey was distributed through social media and at 500-bed pediatrics and maternity hospital in Asir region, at ambulatory care pharmacy. The authors did the patients interview with electronic survey documentation. The survey was made in an electronic format and it analyzed domain two through survey monkey system. Results: The total responders were (614) Saudi patient, the gender distribution 523 (86.7%) were females and 91(13.3%) were males. The majority of them in age (18-44) 78.3% and located at Asir region 325 (115%) and Riyadh region 163 (46.9%). The responders showed no adequate knowledge either complete or incomplete information about the adverse drug reaction either a general side effect of medications 343 (58.5%) only or potential adverse event about their medications 295 (51.2%). The responder showed that they are not aware of contraindication of medicines used with other diseases condition 253 (43.2%), drugs 264 (45.4%), food 277 (47.6 %) or laboratory test 285 (49.5%) and 320 (55.4%) with the herbal drug. The responders showed no adequate knowledge either complete or incomplete information about usage of medications for children 322 (56.46%) or elderly 301 (51.45%), drug use during pregnancy 329 (56.52%) or breastfeeding 319 (54.71%). Conclusion: More than fifty percent of the patients were not familiar with the essential drug-related problems information. It is potential to drug misadventures and cost burden in the society. Very comprehensive and urgent implementation of the patient medications education program in Saudi Arabia is needed.
Keywords: Patient; Knowledge; Misadventure; Medications; Ministry of Health; Saudi Arabia